Comparative methods for chlorophyll detection in leaves - Laura Novac; Catalina Stoica; Anda Gabriela Tenea; Gabriela Geanina Vasile; Mihai Nita-Lazar (Romanian Journal of Ecology & Environmental Chemistry, 2022)
Nowadays, progressive field crop practice requires modern, reliable, and cost-efficient methods to monitor crop development and yield. The most common and used biochemical parameter for plant physiology, namely the dynamic processes of growth, metabolism, reproduction, defense and communication, is chlorophyll's content in plant leaves. Our paper aims to compare optical in-situ method with a classical in vitro spectrometric chlorophyll detection method. A comparison between a quick and cost-effective screening method using portable CCM-200 plus (Opti-Science, Inc) and a biochemical chlorophyll extraction method was applied. Two sets of chlorophyll concentration data from terrestrial plants such as marigold (Calendula officinalis) and wheat (Triticum sp.) were reported. Chlorophyll pigments has a non-uniform distribution on the leaves surface, thus the concentration differs a lot at different times of the day, and this makes the optical measurements vary a lot between the same leaves. In this study, a mathematical correlation of the optical chlorophyll content conversion to absolute chlorophyll was carried out considering previous studies. The relationships between the CCM-200 measurements and the values obtained for the total chlorophyll concentration and the chlorophyll a/b ratio suggested a wide range of relationships between the two species.